PENGARUH PENAMBAHAN BIOADITIF MINYAK ATSIRI PADA BAHAN BAKAR BIOSOLAR TERHADAP KINERJA MESIN DIESEL - Meika Syahbana Rusli; Gilang Ramadhan; Hari Setiapraja; Obie Farobie (Department of Agroindustrial Technology, Bogor Agricultural University, 2022)
B30 is a blend of 30% biodiesel produced from the transesterification process of vegetable oils and 70% diesel derived from fossil fuels. The use of biodiesel is still facing the problems such as high particulate value, water content, and reduced filter life, so it is necessary to improve the fuel-containing biodiesel with bio-additives. This study aimed to determine the effect of bio-additive addition on the characteristics of B30, performance and exhaust emissions of diesel engines, and to determine the best formula from two types of formulas, namely bio additive A (a mixture of turpentine oil, clove terpenes, and citronella) and bio additive B (a mixture of turpentine oil, clove terpene, and rhodinol). The concentration of bio-additive used in the engine performance test was 0.1%. The experimental data was then analyzed using descriptive analysis and one-way ANOVA on the 95% level of characterization testing. The best formula was found in formula B based on the performance test analysis, which increased the torque and power values by 18.09–24.58 Nm and 3.85–5.04 KW, respectively. Furthermore, fuel consumption increased in the bio-additive A by 1,238–1,546 mL/hour and bio-additive B by 1,215 – 1,515 mL/hour. Intriguingly, the CO2 and NOx emissions values decreased by 6–17.6% and 337–1,205 ppm, respectively. Nevertheless, it was observed that the smoke number increased by 2.85 – 6, 45 FSN in bio-additive B. Keywords: B30, biodiesel, bio-additive; diesel engine; essential oil